From hunting-based to nomadic reindeer herding in Røros and surrounding areas (In Norwegian with Summary in English) - Fjellheim, Sverre (Rangifer, 2005)
Until today most researchers have named central Sweden and the Arjeplog area as the cradle of reindeer nomadism. However, there are reasons to believe that the practice of nomadic reindeer herding goes at least as far back in Røros and surrounding areas. The transition was probably initiated by large-scale climatic changes during the 16th and 17th century. Local historian, Anders Reitan, characterises the end of the 16th and the beginning of the 17th century as very difficult for the Røros district, with cold weather and crop failure. He refers to the year 1591 as the "black year", when "the grass didn't turn green north of Dovre", and in 1599 there was "general crop failure throughout northern Europe". 1635 was ostensibly as bad as the "black year", and it was told that in 1647 several people died right next to the trees they had stripped for bark to eat. The cold climate is confirmed by today's climate researchers. In the sources the period from 1550 to 1850 is referred to as "the little ice-age". For the Trøndelag area this meant regular north-westerly and north-easterly winds during the spring, causing later snow-melting and more frequent snowfall and periods of frost than we have today. Summers were shorter and colder, and there was less sun and more rain than in our days. Under such circum¬stances there must have been a good market for meat, which must have put considerable pressure on the wild reindeer stock. However, the cold climate with shortage of food and famine during the 16th and 17th century did not only lead to an increase in the hunting of wild reindeer, but it must also have had a direct influence on the wild reindeer population. Researchers have found that the spring in particular was getting colder during the "little ice-age". And spring weather is of crucial importance to the dynamics of population and the procreative powers of wild reindeer. According to Julie Axman the weather was bad and conditions for the reindeer very difficult in the Røros area around 1867. Reindeer calves died as a result of the long and cold springs, and her father had to borrow money in order to buy more animals. When climatic conditions during the 1860s had such a dramatic impact on the population of wild reindeer, it must have had at least as great consequences in the Røros area during the 16th and 17th century. Even though the reindeer in nomadic times were very tame and under continuous supervision, the herds were left to graze freely on open lands. With the presence of a large population of wild reindeer close to the tame herds, the risk of losing reindeer would be great, especially during winter and in the mating season. The wild reindeer population in Røros would therefore have to be reduced, either before or in parallel to an increase in the number of tame reindeer. The climate contributed to this reduction, and the Sami took care of the rest as far as it was necessary. This could take place in parallel to the building up of herds of tame reindeer. According to the sources there were at least 6 Sami villages in the 17th century, from Tydal in the north to Østerdalen in the south, which kept herds of tame reindeer, and at the same time the Sami population was accused of extinguishing the wild reindeer. A picture emerges. In sum, we can see that circumstances at the time were in favour of a change in strategy, from a hunting-based economy to nomadic reindeer herding.